2022
DOI: 10.7717/peerj.13799
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1-activatied NLRP3 inflammasome induces thrombocytopenia in heatstroke rat

Abstract: Background Thrombocytopenia, an early common complication in heatstroke (HS), has been widely considered as a mortality predictor of HS. The mechanism underlying thrombocytopenia in HS remains unknown. It is not known whether NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome is activated in HS platelet, which, in turn, induces platelet activation and thrombocytopenia. This study tried to clarify the activation of the NOD-like receptor signaling pathway under HS conditions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The main mechanisms include Mb released by RM directly blocking renal tubules, renal injury mediated by oxidative stress and released HMGB1 and H3 mediating liver cell injury and coagulation disorder, eventually leading to more serious organ injury or even death. [1,18,19] Further analysis also found that PCT was associated with RM (Mb≥1,000 ng/mL), DIC, AHI, SOFA score and APACHE II score but not with lymphocytopenia, AKI, or 90-day mortality. The mechanism may be related to the release of intracellular substances into the circulation secondary to RM, which promotes the synthesis of PCT in the liver and leads to severe inflammatory reactions.…”
Section: Discussionmentioning
confidence: 83%
“…The main mechanisms include Mb released by RM directly blocking renal tubules, renal injury mediated by oxidative stress and released HMGB1 and H3 mediating liver cell injury and coagulation disorder, eventually leading to more serious organ injury or even death. [1,18,19] Further analysis also found that PCT was associated with RM (Mb≥1,000 ng/mL), DIC, AHI, SOFA score and APACHE II score but not with lymphocytopenia, AKI, or 90-day mortality. The mechanism may be related to the release of intracellular substances into the circulation secondary to RM, which promotes the synthesis of PCT in the liver and leads to severe inflammatory reactions.…”
Section: Discussionmentioning
confidence: 83%
“…However, the platelet-related pathways have extensive attention owing to its involvement in a variety of cardiac disease processes [ 28 , 29 ]. NOD-like receptor signaling is shown to induce platelet activation during heatstroke [ 30 ] and sepsis [ 25 ]. Human cytomegalovirus directly activates the platelet-derived growth factor system, and human cytomegalovirus-platelet interactions lead to proinflammatory and proangiogenic responses, that exacerbate tissue damage and contribute to atherogenesis [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…iNOS-derived NO triggers the post-translational S-nitrosylation of HMGB1, leading to HMGB1 secretion and proinflammatory responses [151]. Secreted HMGB1 acts in a damageassociated molecular pattern (DAMP), activating the NLRP3 inflammasome [152,153]. Multiple inflammasome-related complications affect immune system homeostasis in patients with severe TBI [154].…”
Section: Astrocyte Activationmentioning
confidence: 99%